Need for Problem-Based Learning in Clinical Pharmacy Education in India - Mateti, Uday Venkat; Konda, Shiv Sagar; Khan, M.G. Irfan Ahmed; Nagappa, Anantha Naik (Indian Journal of Pharmacy Practice)
Problem-Based Learning (PBL) is an instructional student centered approach, which serves to enhance skills such as problem-solving, critical thinking, clinical reasoning and self-directed learning to develop a solution to a defined problem. This review serves the need of changes in the teaching methodology in clinical pharmacy education, where the clinical pharmacy students are involved in elaborative patient care responsibility which embodies exclusive communication skills, increased problem solving capabilities, effective critical thinking abilities and sound decision making skills. As an alternative to current traditional or instructive technique of one way of knowledge transformation from teacher to students, a passive approach where the participation of the student in the learning process is restricted. It also creates an environment for student group dynamics in an open PBL setting. In this model a mentor should act as a facilitator rather than an instructor. The PBL incorporates basic elements of learning and integrate theory and practice and relates the basic to the applied knowledge. Furthermore there is a need to validate the effectiveness of PBL with conventional class room teaching. Unless the practical problems are not posed to the students the development of accessible effective knowledge is not achieved. Hence the PBL ensures highest participation of the students. Thus the PBL can be incorporated in the future clinical pharmacy practice curriculum to make PharmD course an effective in training skilled clinical pharmacist.
Keywords: Problem Based Learning; India; Pharmacy; Education; PharmD